The effect of using the Geometry Pad on geometric achievement and revealing geometric fallacies among fifth-grade primary school students - Al-Saadi, Mustafa Raad AbdUlrasool (Journal of Curriculum and Teaching Methodology, 2025)
The research aimed to investigate the effect of using the Geometry pad on geometric achievement and detecting geometric fallacies among fifth-grade primary school students. To verify the research objectives, the quasi-experimental design was adopted for (two equivalent experimental-control groups) with a post-test. The experiment was applied to a sample of fifth-grade primary school students, numbering (78) students, with (40) students for the experimental group and (38) students for the control group for the academic year (2022-2023). They were rewarded in several variables indicated in the text of the research. The research tools represented by the Geometry Achievement Test and the Geometry Fallacy Detection Test were built, and their statistical and psychometric properties were verified.The results showed that the students of the experimental group who studied using the Geometry pad outperformed the students of the control group who studied according to the usual method in the Geometry Achievement Test and the Geometry Fallacy Detection Test.The research came out With a number of recommendations, the most important of which is emphasizing the use of technological innovations and the applications provided by tablets and portable devices that support the teaching of mathematics, and some suggestions established in the text of the research.